2020
DOI: 10.1080/22797254.2020.1762247
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Monitoring soil salinization in Manas River Basin, Northwestern China based on multi-spectral index group

Abstract: Large-scale and accurate monitoring soil salinization is essential for controlling soil degradation and sustainable agricultural development. The agricultural irrigation area of the Manas River Basin in the arid area of Northwest China was selected as the test area. The soil salinization monitoring model based on spectral index group was constructed by comparing the accuracy of PCR, PLSR and MLR models using the transformation of multi-spectral index group and index screening. The results showed that there was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…The soil characteristics are impacted by various factors (e.g., vegetation cover, moisture, texture, parent material, etc. ), which must be considered in soil salinity mapping 39 , 40 . Therefore, we applied the Combined Spectral Response Index (CSRI) technique to compute the soil salinity ratio for each study year.…”
Section: Methodsmentioning
confidence: 99%
“…The soil characteristics are impacted by various factors (e.g., vegetation cover, moisture, texture, parent material, etc. ), which must be considered in soil salinity mapping 39 , 40 . Therefore, we applied the Combined Spectral Response Index (CSRI) technique to compute the soil salinity ratio for each study year.…”
Section: Methodsmentioning
confidence: 99%
“…For example, Fu et al [10] performed root mean square ( √ R), reciprocal (1/R), inverse logarithmic (log(1/R)), logarithmic, and logarithmic reciprocal preprocessing after Savitzky-Golay (SG) convolution smoothing on the raw spectra and found that the model accuracy constructed based on SG smoothing and 1/R preprocessing was the highest. Shi et al [11] performed logarithmic, exponential, and square root (R 1/2 ) preprocessing on raw spectral data to construct spectral indices and found that preprocessing obviously improved the soil salinity estimation accuracy compared with the raw spectra data, especially R 1/2 preprocessing. Wang and Li [12] constructed support vector regression (SVR) models after preprocessing raw spectral data using average reflectance (R), the logarithm of the reciprocal of R, and the continuum removal of reflectance (Rcr), and they found that the R-based and Rcr-based SVR model had the highest accuracy in estimating soil Cl − and K + content, respectively.…”
Section: Introductionmentioning
confidence: 99%